2013
DOI: 10.1109/tcst.2013.2261069
|View full text |Cite
|
Sign up to set email alerts
|

Design Tradeoffs of Wind Turbine Preview Control

Abstract: Recent work has demonstrated the benefits of preview wind measurements for turbine control. This paper investigates the basic design trade-offs between turbine performance, preview time, and pitch actuator rate limits. A Region 3 rotorspeed tracking problem is formulated in continuous-time as an optimal control problem using a simple one-state rigid body turbine model. The exact, analytical solution to this problem provides insight into the fundamental performance limits. These analytical results are compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…The current decade literature has presented new structure, systems, and generalizations in the design of preview control. The solution to preview control design problem is proposed for nonminimum phase systems, linear descriptor discrete‐time systems, and systems with stochastic parameter uncertainties . The classical solution of H ∞ preview control design is generalized for both previewable and unpreviewable disturbances, also .…”
Section: Classification Of Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…The current decade literature has presented new structure, systems, and generalizations in the design of preview control. The solution to preview control design problem is proposed for nonminimum phase systems, linear descriptor discrete‐time systems, and systems with stochastic parameter uncertainties . The classical solution of H ∞ preview control design is generalized for both previewable and unpreviewable disturbances, also .…”
Section: Classification Of Literaturementioning
confidence: 99%
“…Kristalny et al has proposed a frequency‐domain‐based solution for preview control that is beneficial as the equations framed does not depend on preview length. This approach is extended to include the distortion model in the problem formulation and is presented for wind turbine towers .…”
Section: Classification Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Many interesting results have been reported [1][2][3]. Applications of the preview control have been found in many areas such as active vehicle suspensions, robotics, and wind turbines [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Finally an optimal preview controller was obtained by the extremum principle. Due to decades of research, preview control not only has made a major theoretical breakthrough (e.g., preview control theory of multirate systems, time-varying systems, continuous-time stochastic systems, and so on [4][5][6][7]), but it also has been used successfully in many other areas [8][9][10].…”
mentioning
confidence: 99%